(untitled) (European Journal of Marketing and Economics, 2024)
This paper investigates the long-term relationship between Foreign Direct Investment (FDI) and economic growth in Turkey, emphasizing the strategic role of international capital flows in fostering national development. Rooted in economic theory that links FDI to GDP growth through knowledge spillovers, technology transfer, and productivity gains, the study analyzes time-series data from 1980 to 2017. The Johansen cointegration test confirms the presence of a stable long-run equilibrium relationship between FDI inflows and GDP, indicating that FDI has contributed to Turkey’s macroeconomic growth trajectory. In the short run, Granger causality analysis demonstrates a unidirectional causality running from FDI to GDP, reinforcing the view that foreign investment has functioned as a driver rather than merely a consequence of economic performance. These results underscore the importance of creating a favorable investment climate and targeting sectors that can maximize the developmental benefits of FDI. The paper offers valuable implications for policymakers and international investors seeking to understand the dynamics of growth in emerging markets and highlights the strategic importance of FDI in Turkey’s economic policy framework.